Community-Acquired Pneumonia Caused by Mycoplasma pneumoniae: How Physical and Radiological Examination Contribute to Successful Diagnosis - Kishaba, Tomoo (Frontiers in Medicine, 2016)
Mycoplasma pneumoniae is one of the most common causes of community acquired pneumonia, particularly in young adults. Vital signs are usually normal except for temperature. On physical examination, general appearance is normal compared with that of typical pneumonia such as pneumococcal pneumonia patients. Mycoplasma sometimes causes ear infections such as otitis media. It is important to distinguish between typical pneumonia and atypical pneumonia such as mycoplasma pneumonia because having the right diagnosis allows for the use of the correct antibiotic to treat community-acquired pneumonia while preventing development of drug-resistant bacteria and also decreasing medical cost. The symptoms and diagnosis of mycoplasma pneumonia is multi-fold. Auscultation of patients can demonstrate trace late inspiratory crackles or normal alveolar sounds; however, bilateral polyphonic wheezes can sometimes be heard because of bronchiolitis. With regard to radiological findings, a chest radiogragh often shows bilateral reticulonodular or patchy consolidation in both lower lobes. Pleural effusion is rarely observed in adult cases. Immunocompetent patients tend to reveal more extensive shadowing compared with immunocompromised patients. As serological diagnostic methods are not able to offer 100% reliable diagnosis, integration of physical and radiological examination is crucial to accurately diagnose mycoplasma pneumonia. Herein, I review the typical findings from physical examination and imaging patterns of patients with mycoplasma pneumonia.